Sustainable Development of Seaport Cities through Circular Economy: A Comparative Study with Implications to Suez Canal Corridor Project - Ezzat, Ahmed Mohamed (European Journal of Sustainable Development, 2016)
As seaport cities have large potential for commercial, tourist and industrial activities, they are considered one of the main driving forces of economic growth. At the same time, the localization of these activities in seaport cities can be a source of new economic, social and ecological damage for the whole seaport city system. Accordingly, the development of the seaport city system tends to become less sustainable despite the growing trend to focus on sustainable development through ensuring sustainable consumption and production patterns. The study focuses on adopting the circular economy model in seaports cities as a mean to enhance sustainable development. The study used the analytical method showing the theoretical preview of circular economy, the potential opportunities of adopting circular economy and the comparative method to show the best practices of circular economy in seaport cities. Then the results were used to evaluate the Suez Canal Corridor Project. Both theoretical and empirical best practices stressed the rule of adopting a circular economy model in supporting seaport cities sustainable development. The conclusion for the Suez Canal Corridor Project was that some of the dimensions of the circular economy model are missing including the legislative, institutional and cultural issues. Those can be considered as challenges to the contribution of the project to bring sustainable development. Keywords: Port sustainable Development, Development of seaport cities, Greening the economy, the circular economy model and the Suez Canal Corridor Project.